Peasant’s Training as an Instrument for the Transformation of Andean Agriculture - Solís Mora, José (2016)
The essay shows how methods of peasant training which are designed according to the interests of producers and according to their context have positive results. This case corroborates the changes in livelihoods of peasant promoters called kamayoq, that took place along ten years in the Cuzco Andes. It proves that it is possible to develop the rural economy improving peasant’s skills.